A Major Fimbrilin Variant of Mfa1 Fimbriae in Porphyromonas gingivalis. (August 2015) - Nagano, K.; Hasegawa, Y.; Yoshida, Y.; Yoshimura, F.
The periodontal pathogen Porphyromonas gingivalis is known to express 2 distinct types of fimbriae: FimA and Mfa1 fimbriae. However, we previously reported that fimbria-like structures were found in a P. gingivalis strain in which neither FimA nor Mfa1 fimbriae were detected. In this study, we identified a major protein in the bacterial lysates of the strain, which has been reported as the 53-kDa major outer membrane protein of P. gingivalis (53K protein) and subsequently reported as a major fimbrilin of a novel-type fimbria. Sequencing of the chromosomal DNA of the strain showed that the 53k gene (encoding the 53K protein) was located at a locus corresponding to the mfa1 gene (encoding the Mfa1 protein, which is a major fimbrilin of Mfa1 fimbriae) of the ATCC 33277 type strain. However, the 53K and Mfa1 proteins showed a low amino acid sequence homology and different antigenicity. The 53K protein was detected in 34 of 84 (41%) P. gingivalis strains, while the Mfa1 protein was detected in 44% of the strains. No strain expressed both 53K and Mfa1 proteins. Additionally, fimbriae were normally expressed in mutants in which the 53k and mfa1 genes were interchanged. These results indicate that the 53K protein is another major fimbrilin of Mfa1 fimbriae in P. gingivalis .